2002
DOI: 10.1046/j.1523-1755.2002.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional effects of renal artery stent placement on treated and contralateral kidneys

Abstract: Renal artery stenting was capable of causing improvement of glomerular filtration rate of the treated kidney, although the overall glomerular filtration rate did not change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…In unilateral renal artery stenosis, the unobstructed kidney is capable of compensating for the contralateral stenotic kidney by increasing its GFR. 24,25 After revascularization, however, the compensatory increase in GFR of the nonobstructed kidney returns to baseline, and the overall GFR remains unaltered. Although BNP has been reported to be elevated in patients with a GFR Ͻ60 mL · min Ϫ1 · 1.73 m Ϫ2 , 26 our data demonstrated no statistical significant difference for elevated BNP (Ͼ80 pg/mL) stratified for an eGFR Ͻ60 or Ͼ60 mL · min Ϫ1 · 1.73 m Ϫ2 (92% versus 67%; Pϭ0.14).…”
Section: Discussionmentioning
confidence: 99%
“…In unilateral renal artery stenosis, the unobstructed kidney is capable of compensating for the contralateral stenotic kidney by increasing its GFR. 24,25 After revascularization, however, the compensatory increase in GFR of the nonobstructed kidney returns to baseline, and the overall GFR remains unaltered. Although BNP has been reported to be elevated in patients with a GFR Ͻ60 mL · min Ϫ1 · 1.73 m Ϫ2 , 26 our data demonstrated no statistical significant difference for elevated BNP (Ͼ80 pg/mL) stratified for an eGFR Ͻ60 or Ͼ60 mL · min Ϫ1 · 1.73 m Ϫ2 (92% versus 67%; Pϭ0.14).…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have documented that renal artery stent placement improves or stabilizes renal function in patients with atherosclerotic RAS (749)(750)(751)(752). Significant improvement in renal function up to 1 year after unilateral renal artery stent placement was demonstrated by Leertouwer and coworkers (701). They demonstrated that the glomerular filtration rate in the revascularized kidney improved significantly but that overall glomerular filtration rate from both kidneys did not change (721).…”
Section: Class Iib Percutaneous Revascularization May Be Considered Fmentioning
confidence: 96%
“…Revascularization is effective in stabilizing or improving renal function in patients with symptomatic atherosclerotic RAS (701,(744)(745)(746)(747)(748). Several trials have documented that renal artery stent placement improves or stabilizes renal function in patients with atherosclerotic RAS (749)(750)(751)(752).…”
Section: Class Iib Percutaneous Revascularization May Be Considered Fmentioning
confidence: 99%
“…All presented significant atherosclerotic mmHg in the lesion). Patients were referred to renal artery angioplasty with placement of a stent according to the clinical history and physical examination analyzed in conjunction with stenosis of renal artery suggested by the renal US-Doppler and with the results of renal arteriography, similarly to procedures recommended and performed in other previous studies [14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small number of patients involved in this study, the sample tried to select the cases with a clear clinical indication for percutaneous renal revascularization, either to control systemic hypertension or to preserve or restore renal function 3,12,20,21 . In fact, several studies have evaluated the renal function after renal angioplasty with stent placement 10,11,[16][17][18][20][21][22][23] . A study carried out by Jensen 24 evaluated 107 patients with ARAS in a one-year follow-up after stenting in renal artery and found that this group showed decreased BP and increased glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%